The Effect Of Dictogloss Technique To The Writing Skill Of Eight Grade Of Smp Negeri 7 Pematangsiantar In Descriptive Text - Lasmaria Tiodora Silviana Sitinjak; Selviana Napitupulu; Bertaria Sohnata Hutauruk (Lembaga Riset dan Inovasi Almatani, 2026)
This research aimed to examine the effect of the Dictogloss Technique on students’ writing ability in descriptive text at the eighth grade of SMP Negeri 7 Pematangsiantar. This research applied a quantitative method with a quasi-experimental design. The population of this study was the eighth-grade students in the academic year 2025/2026. The sample consisted of two classes, namely VIII-5 as the experimental class and VIII-6 as the control class, with 30 students in each class. The data were collected through writing tests in the form of pre-test and post-test administered to both classes. The results showed that the mean score of the experimental class improved from 61.13 in the pre-test to 81.53 in the post-test. Meanwhile, the control class increased from 66.80 to 77.50. The data were analyzed by using the t-test formula. The result revealed that the t-test value (2.500) was higher than the t-table value (1.671) at the 5% level of significance. Based on the findings, the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. It can be concluded that the Dictogloss Technique has a significant effect on students’ writing ability in descriptive text at the eighth grade of SMP Negeri 7 Pematangsiantar.